2019
DOI: 10.15587/1729-4061.2019.185111
|View full text |Cite
|
Sign up to set email alerts
|

Development of nanomodified rapid hardening clinker-efficient concretes based on composite Portland cements

Abstract: Liquid glass and aqueous solutions of silicates, as a promising basis for technological processes of new nanocomposite materials. Inzhenerniy vestnik Dona.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…When determining the indicators of free energy of the surface, it is established that with an increase in the amount of titanium dioxide in the volume of the mortar, the energy of the surface decreases, which indicates the improvement of the operational characteristics of such mortars. 4. It has been determined that the improved characteristics are achieved when adding 2.0 wt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When determining the indicators of free energy of the surface, it is established that with an increase in the amount of titanium dioxide in the volume of the mortar, the energy of the surface decreases, which indicates the improvement of the operational characteristics of such mortars. 4. It has been determined that the improved characteristics are achieved when adding 2.0 wt.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental characteristic of cement systems, which largely determines their properties, is their granulometric composition, determined by the particle size distribution. The average diameter per volume D [4,3] for Portland cement CEM II/B-M is 26.3 µm, with the average diameter per specific surface D [3,2] corresponds to 4.02 µm. For the Portland cement СЕМ ІІ/В-М, the residue on a sieve of 45 µm is 12.6 wt.…”
Section: Studying the Particle Size Distribution In Cement Systemsmentioning
confidence: 99%
“…Many studies have confirmed that the surface activity of NS with cement, during the hydration process, is much higher than that of SF and cement, as a result of which the consumption rate of CH is much higher in the case of NS. Moreover, the volume fraction of the high-stiffness C-S-H gel increases significantly in NS-modified specimens, as compared to SF-modified ones [15][16][17].…”
Section: Isothermal Calorimetrymentioning
confidence: 91%
“…Due to the environmental impact of the cement industry in the direction of sustainable development, by selecting appropriate combinations of non-clinker components in low-carbon cements will be an alternative to traditional cements [10][11][12][13]. At the same time, more and more attention are paid to the production of lowcarbon concretes.…”
Section: Introductionmentioning
confidence: 99%